Satisfaction and associated side effects of commercially available hand sanitizer during the time of COVID-19 pandemic among health professional of Kathmandu Nepal. - Mahotra, Narayan Bahadur (2021)
EXECUTIVE SUMMARY: Introduction: The World Health Organization declared the outbreak of SARS COV-2 a public health emergency of international concern on 30 January 2020, and a pandemic on second week of March 2020. With this novel corona virus outbreak terms such as "Quarantine", "Contact Tracing" and "Hand Sanitizers" have also gained popularity among the general public. Hand sanitizer is a liquid/gel/foam used to disinfect hands instantly. It is considered as convenient method of disinfecting hands where water and soap are not readily available. Hand sanitizer have variety of chemical as their active ingredient but broadly classified as Alcohol based and non-Alcohol based. Hand sanitizer is able to disinfect a large number of microorganisms such as Escherichia coli, Serratia marcescens and Staphylococcus saprophyticus etc. However, hand washing has more merits than that of sanitizer. Hand sanitizers sometimes can cause side effects such as skin redness, dryness, cracks, and even blisters that cause itching or pain. Methodology: A descriptive cross-sectional study design was carried out to assess the usefulness and associated adverse effects of hand sanitizer in health professionals of Kathmandu, Nepal during COVID-19 Pandemic. And it was conducted among health professionals of Kathmandu, Nepal from March 2021 to June 2021. Data collection tools were developed on the basis of the literature reviews available of the respected fields. Some tools were adopted and made contextual for field setting. These tools were finalized in close consultation with experts. The questionnaires were coded using a google form-based data application and data were collected using online platform. Results: In results, we found that majority of the participants used alcohol-based sanitizer (98.3%) while only 1.7% of them used non-alcohol-based sanitizer. Majority of the participants were neutral regarding whether they like the smell of sanitizer or not. Similarly, majority of participants disagree on effectiveness of the hand sanitizer is directly dependent to its price. Majority of participants agreed on the statement "hand sanitizer that I use works properly". But most of the participants showed neutrality on recommending same sanitizer to others. Majority of the participants felt safe from COVID 19 as they were using hand sanitizer frequently. Similarly, most of the participants disagreed that they need not to wash hands as they were using hand sanitizer frequently and majority were neutral on use of commercially available hand sanitizer has side effects on health in long run. But majority of participants (70.14%) didn't show any side effect of sanitizer while 29.86 % showed side effect. Conclusion: This research is concluded that majority of the hand sanitizer users felt that the hand sanitizer was safe and they believed that the sanitizer they are using works properly as well. And most of the sanitizer's users did not experience any side effect. Keywords: COVID-19 pandemic; Hand sanitizer; Health professional, Kathmandu